Ratings are Overrated! - Yannakakis, Georgios N.; Martínez, Héctor P. (Frontiers in ICT, 2015)
Are ratings of any use in human-computer interaction and user studies at large? If ratings are of limited use, is there a better alternative for quantitative subjective assessment? Beyond the intrinsic shortcomings of human reporting, there are a number of supplementary limitations and fundamental methodological flaws associated with rating-based questionnaires --- i.e. questionnaires that ask participants to rate their level of agreement with a given statement such as a Likert item. While the effect of these pitfalls has been largely downplayed, recent findings from diverse areas of study question the reliability of using ratings. Rank-based questionnaires --- i.e. questionnaires that ask participants to rank two or more options --- appear as the evident alternative that not only eliminates the core limitations of ratings but also simplifies the use of sound methodologies that yield more reliable models of the underlying reported construct: user emotion, preference, or opinion. This paper solicits recent findings from various disciplines interlinked with psychometrics and offers a quick guide for the use, processing and analysis of rank-based questionnaires for the unique advantages they offer. The paper challenges the traditional state-of-practice in human-computer interaction and psychometrics directly contributing towards a paradigm shift in subjective reporting.